Microsoft® Excel® 2016 bible - Walkenbach, John (Wiley, 2015)
The complete guide to Excel 2016, from Mr. Spreadsheet himself Whether you are just starting out or an Excel novice, the Excel 2016 Bible is your comprehensive, go-to guide for all your Excel 2016 needs